Model for selecting a route for the transport of hazardous materials using a fuzzy logic system - Milošević, Teodora D.; Pamučar, Dragan S.; Chatterjee, Prasenjit (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The paper presents a model for the selection of a route for the transport of hazardous materials using fuzzy logic systems, as a type of artificial intelligence systems. The system presented in the paper is a system for assistance in the decision-making process of the traffic service authorities when choosing one of several possible routes on a particular path when transporting hazardous materials.Methods: The route evaluation is performed on the basis of five criteria. Each input variable is represented by three membership functions, and the output variable is defined by five membership functions. All rules in a fuzzy logic system are determined by applying the method of weight premise aggregation (ATPP), which allows the formation of a database based on experience and intuition. Based on the number of input variables and the number of their membership functions, the basic base of 243 rules is defined. Three experts from the Ministry of Defense were interviewed to determine the weighting coefficients of the membership functions, and the values ​​of the coefficients were determined using the Full Consistency Method (FUCOM).Results: A user program which enables the practical application of this model has been created for the developed fuzzy logic system.Conclusion: The user platform was developed in the Matlab 2008b software package.
Keywords: Fuzzy logic; Fuzzy set; ATPP; FUCOM; hazardous materials; Matlab